2015
DOI: 10.3122/jabfm.2015.01.130323
|View full text |Cite
|
Sign up to set email alerts
|

BREATHE OUT: A Randomized Controlled Trial of a Structured Intervention to Improve Clinician Satisfaction With "Difficult" Visits

Abstract: Purpose: Difficult patients comprise at least 15% of ambulatory visits and are associated with clinician burnout. No structured procedure has been reported to assist health care practitioners with these challenging relationships. This randomized trial evaluated whether a pre-and postvisit patient-centered and clinician-reflective technique called BREATHE OUT improved clinician satisfaction during visits with patients perceived by the clinician as difficult.Methods: Six family medicine residency clinics paired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…One example is the BREATHE OUT technique, which includes a structured pre-visit intervention with the mnemonic BREATHE to prompt 1) reflection on provider's Bias or assumption about the patient, 2) reflection upon why patient is difficult, 3) goals to accomplish during the visit, and 4) pause before entering the patient room, as well as a post-visit intervention mnemonic OUT to prompt 1) reflection on the outcome, 2) consideration regarding whether anything unexpected was learned, and 3) anticipation of what the provider would look forward to addressing tomorrow. This BREATHE OUT technique has been shown to improve physician satisfaction with DPEs [ 26 ]. These techniques may support residents’ resilience on an individual level, although systems interventions to optimize the learning and working environment, which go beyond the scope of a difficult encounters curriculum, remain important steps to reducing resident anxiety and burnout [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…One example is the BREATHE OUT technique, which includes a structured pre-visit intervention with the mnemonic BREATHE to prompt 1) reflection on provider's Bias or assumption about the patient, 2) reflection upon why patient is difficult, 3) goals to accomplish during the visit, and 4) pause before entering the patient room, as well as a post-visit intervention mnemonic OUT to prompt 1) reflection on the outcome, 2) consideration regarding whether anything unexpected was learned, and 3) anticipation of what the provider would look forward to addressing tomorrow. This BREATHE OUT technique has been shown to improve physician satisfaction with DPEs [ 26 ]. These techniques may support residents’ resilience on an individual level, although systems interventions to optimize the learning and working environment, which go beyond the scope of a difficult encounters curriculum, remain important steps to reducing resident anxiety and burnout [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ecological momentary assessment may prove beneficial for designing a study to investigate cumulative effects of informal practices -this would consist of randomly paging HCPs to practice informally and then measuring the effects on patient care outcomes relative to a group of HCPs not practicing informal mindfulness. This was preliminarily investigated in a recent study with findings supported by our grounded theory model - Edgoose and colleagues (2015) found that an informal practice at work improved HCP-perceptions of difficult patient encounters (Edgoose et al, 2015). Another method for investigating informal practices may be to follow the example by Edgoose et al, 2015, and measure HCP and patient outcomes prior to and following an encounter in which the HCP practices informal mindfulness immediately before the patient encounter and immediately after the baseline outcome measurement.…”
Section: Aim 7 Grounded Theory Explorationmentioning
confidence: 97%
“…This was preliminarily investigated in a recent study with findings supported by our grounded theory model - Edgoose and colleagues (2015) found that an informal practice at work improved HCP-perceptions of difficult patient encounters (Edgoose et al, 2015). Another method for investigating informal practices may be to follow the example by Edgoose et al, 2015, and measure HCP and patient outcomes prior to and following an encounter in which the HCP practices informal mindfulness immediately before the patient encounter and immediately after the baseline outcome measurement. This would provide information on the state-effects of informal practices as opposed to cumulative, or trait, effects.…”
Section: Aim 7 Grounded Theory Explorationmentioning
confidence: 97%
See 1 more Smart Citation
“…Physicians who report many of these types of patient encounters are more likely to be dissatisfied in practice. In a randomized trial across 6 offices, Edgoose et al 1 report the positive results of a structured, angstrelieving, reflective intervention used by the provider before and after these visits. "BREATHE" is the mnemonic used for the portion of the intervention before the visit, and "OUT" is the mnemonic for the portion used after the visit.…”
Section: Interventions For the Individual Providermentioning
confidence: 99%